Policy rules for inflation targeting - Glenn D. Rudebuschy; Lars E. O. Svensson (Sveriges Riksbank, 1998)
Policy rules that are consistent with inflation targeting are examined in a small macro-econometric model of the US economy. We compare the properties and outcomes of explicit instrument rules as well as targeting rules. The latter, which imply implicit instrument rules, may be closer to actual operating procedures of inflation-targeting central banks. We find that inflation forecasts are central for good policy rules under inflation targeting. Some simple instrument and targeting rules do remarkably well relative to the optimal rule; others, including some that are often used as representing inflation targeting, do less well.
Keywords: 330